Effect of processing on dielectric properties of (0.95)PbZr 0.52Ti0.48O3-(0.05)BiFeO3 - Sharma S.; Singh V.; Parkash O.; Dwivedi R.K. (My University, 2025)
An effort has been made to synthesize solid solution of a composition with x=0.05 in the system (1-x)PbZr0.52Ti0.48O 3-(x)BiFeO3 by the sol-gel method. XRD patterns of the pure PZT and BFO modified PZT samples have shown single phase formation. The effects of substitution of BFO on dielectric properties of PZT have been studied in the frequency range 10 Hz to 100 kHz and temperature range from RT to 773 K. The density was optimized by sintering the BFO modified PZT samples at different temperatures in four batches, S1, S2, S3 and S4. P-E hysteresis loop measurements for all the samples have shown almost saturated polarization. It has been observed that sample S2, sintered at 950 C, exhibits superior dielectric properties of the four samples. The occurrence of weak ferromagnetism, observed in the M-H hysteresis loop, indicates coupling between ferroelectricity and magnetism. Impedance analysis has revealed that all the samples, sintered at different temperatures, have a different grain resistance. A large change in ac conductivity around T c has been observed in all the samples. © 2012 Springer-Verlag Berlin Heidelberg.